Endodontic Intervention for the Control of Periapical Injury Associated with Traumatized Teeth: A Case Report - Fabiane Fernandes; Jefferson Pires Silva Júnior; Bruna Mirely Cavalcante; Laíz Fernanda Almeida; Naildo Cordeiro; André Luiz Silva (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
The incidence of patients affected by dental trauma is quite frequent. The treatment of choice should be selected according to the severity level of dental trauma in odontology. Periapical injuries caused by trauma can lead to a rupture of the pulpal blood supply. The objective of the present paper is to present a clinical case of endodontic therapy on two necrotic teeth with a periapical lesion resulting from dental trauma. A 36-year-old patient, male, melanoderma, normosystemic, attended the Nilton Lins University Dental Clinic reporting anterior region discomfort on chewing. He also complained about his smile due to tooth darkening. Sensibility tests were performed, confirming a state of necrosis in teeth 11 and 12. In the periapical radiographs, the teeth presented a radiolucent, circumscribed image delimited in the root apex region, suggesting periapical injury. Based on clinical and radiographic findings, the proposed treatment was pulpectomy with subsequent endogenous bleaching. The endodontic intervention was performed in two sessions after exposure to intracanal medication and endogenous bleaching in four sessions, using the association of 37% Whiteness carbamide peroxide and 20% Whiteness sodium perborate. The success or failure of endodontic treatment with a periapical lesion is related to the control of the infection associated with the healing response, whether partial or total. The treatment proved effective after one year of follow-up, supported by the clinical characteristics combined with the radiographic findings, promoting the return of the teeth to their aesthetic and functional capacities, meeting the expected expectations. The patient is under follow-up.